Technologies For Developing Management Competence of Leaders of Non-Government Preschool Education Organizations - Fotima Olimjonovna Haqqiyeva (Euro Asian Journal Publishing, 2023)
This article provides information on the development of management competence of the heads of preschool education organizations based on publicprivate partnership, modern mechanisms of the development of the non-state sector in the field of preschool education
Keywords: Public private partnership; Preschool education organization; innovative approach